O atendimento individual na área de língua portuguesa de um CEEBJA : aspectos organizacionais e pedagógicos - Carvalho, Maria de Lourdes Andrade de (2013)
People and even educators and researchers from other scientific areas, as a rule, link the Education of Young People and Adults (EJA) to the Mobral program, featuring the eradication of illiteracy, and to Fast Education. Few acknowledge this type of education as a modality of Basic Education based on the 1988 Brazilian Constitution and on the 1996 Guidelines for National Education. Although the number of research works on Education of Young People and Adults has increased, most are limited to educational areas and focus on public policies and/or the literacy during the first years of Basic Education. The above procedure fails to explore the last years of Basic Education (Phase II) and High School. Since the author is a teacher in the Education of Young People and Adults, she characterizes individual attendance to students in the area of Portuguese Language in a State Centre of Basic Education for Young People and Adults Professor Manoel Rodrigues da Silva (CEEBJA) so that EJA may be seen as a teaching modality in Basic Education and discussions may be encouraged on pedagogical practices and their relationship with interactivities in the classroom, among professionals, especially within courses for teacher formation. Current qualitative-interpretative research is a case study, with ethnographic overtones, which focuses on individual attendance and pedagogical practices developed by teachers of Portuguese. Research also describes and debates such attendance. The history of EJA with a brief analysis of Basic Education modality in Brazil and in the state of Paraná is first discussed. Documentary surveys and a revision of the literature underscore changes which occurred in adult education. Interviews and official documents were investigated for the reconstruction of the CEEBJA in Maringá PR Brazil since its establishment up to 2012, coupled to its bonding with personal attendance. Personal attendance and pedagogical practices in the Portuguese Language are described from half-structured interviews with teachers who practice personal attendance and from questionnaires answered by students. Results show that individual attendance of CEEBJA is a differentiated organization whose main features go beyond timetable flexibility. In fact, they comprise different forms of relationships and institutional interactions foregrounded on the students learning type and learning.